Scintillation properties of europium doped RbCaCl₃ crystals - Rebrova, N.V.; Grippa, A.Yu.; Pushak, A.S.; Gorbacheva, T.E.; Pedash, V.Yu.; Cherginets, V.L.; Tarasov, V.A. (Functional Materials, 2017)
The scintillation properties of RbCa₁₋ₓEuₓCl₃ (x = 0.005, 0.03, 0.05, 0.08) single crystals grown from the charge obtained by the solution routine using the Bridgman-Stockbarger method are reported. The luminescence spectra of RbCa₁₋ₓEuₓCl₃ crystals show a single band with a maximum which position shifts from 437 to 443 nm with increase of mole fraction of Eu²⁺ from 0.005 to 0.08. The decay of the scintillation pulse can be described using single component and the decay time rises towards concentration of Eu²⁺ in crystals. The relative light yield achieves 55 per cent vs. NaI:Tl for RbCa₀.₉₂Eu₀.₀₈Cl₃ sample.